2011
DOI: 10.1007/s00442-011-2176-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein storage and root:shoot reallocation provide tolerance to damage in a hybrid willow system

Abstract: To determine the mechanistic basis of tolerance, we evaluated six candidate traits for tolerance to damage using F(2) interspecific hybrids in a willow hybrid system. A distinction was made between reproductive tolerance and biomass tolerance; reproductive tolerance was designated as a plant's proportional change in catkin production following damage, while biomass tolerance referred to a plant's proportional change in biomass (i.e., regrowth) following damage. F(2) hybrids were generated to increase variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 84 publications
0
20
1
Order By: Relevance
“…Leaf damage can also increase the photosynthetic efficiency of plant tissue (Thomson et al, 2003;Stevens et al, 2008) suggesting that the loss of photosynthetic tissue in damaged portions of the plant may be additively beneficial to the undamaged portions as these plant parts will benefit from increases in both photosynthetic capacity and light radiation. Further, storage of proteins and carbohydrates may also function as tolerance mechanisms (Myers and Kitajima, 2007;Babst et al, 2008;Hochwender et al, 2011). For example, damaging insects may induce transport responses of carbon within woody plants (Babst et al, 2008) which potentially could induce rapid growth in remaining plant tissue.…”
Section: Morphological Growth Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf damage can also increase the photosynthetic efficiency of plant tissue (Thomson et al, 2003;Stevens et al, 2008) suggesting that the loss of photosynthetic tissue in damaged portions of the plant may be additively beneficial to the undamaged portions as these plant parts will benefit from increases in both photosynthetic capacity and light radiation. Further, storage of proteins and carbohydrates may also function as tolerance mechanisms (Myers and Kitajima, 2007;Babst et al, 2008;Hochwender et al, 2011). For example, damaging insects may induce transport responses of carbon within woody plants (Babst et al, 2008) which potentially could induce rapid growth in remaining plant tissue.…”
Section: Morphological Growth Responsesmentioning
confidence: 99%
“…Mechanisms mediating tolerance may be many; e.g. patterns in resource allocation (Canham et al, 1999;Eyles et al, 2009) and storage (Myers and Kitajima, 2007;Babst et al, 2008;Hochwender et al, 2011), photosynthetic activity (Thomson et al, 2003), phenology and plant architecture (Fornoni, 2011) and the mechanism through which tolerance is expressed may also vary with the type of damage received (the identity of the damaging herbivore). For example, removal of photosynthetic tissue may be compensated through increased photosynthetic ability of remaining tissue whereas when subjected to loss of woody biomass the plant may depend more on a resource storage mechanism (Marquis, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…This may also indicate that both growth and reserves suffer from resource limitation. In parallel, earlier studies similarly reported that defoliation can influence the mobilization and storage of NSC between sinks and sources depending on resource availability (Babst et al, 2008; Schwachtje et al, 2005; Hochwender et al, 2012). However, our results contradict the results of Rivera-Solís et al (2012) who found higher carbon accumulation in roots of defoliated Ruellia nudiflora –a perennial herb–relative to non-defoliated plants.…”
Section: Discussionmentioning
confidence: 54%
“…We interpreted the large differences in root biomass between control and defoliated seedlings in a resource limited environment as a result of two main co-occurring processes: (a) after defoliation, translocation of photoassimilates from foliage to roots is severely reduced, which in turn reduces root growth, and (b) as new stem buds are activated to produce new leaves, roots translocate reserves to promote active growth in these carbohydrate sinks, which further compromises root growth. These predictions are based on the assumption that defoliation alters resource allocation in woody plants (Babst et al, 2008; Stevens, Kruger & Lindroth, 2008; Najar et al, 2014) and resources are utilized for growth of remaining plant tissues, particularly leaves (Landhäusser & Lieffers, 2002; Babst et al, 2008; Hochwender et al, 2012). Furthermore, substantial allocation of resources to roots may not be advantageous to early successional tree species–like aspen, because increasing above ground biomass, such as leaves and stems, may improve aspen’s competitive ability to capture lights.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation